Transitioning to sustainable energy: opportunities, challenges, and the potential of blockchain technology - Lv, Yongjun (Frontiers in Energy Research, 2023)
The pressing issues of climate change and the limited availability of non-renewable energy resources have created a growing need for sustainable energy alternatives. This study provides a comprehensive overview of the pressing need for sustainable energy solutions and the complex relationship between energy and the economy. The challenges and opportunities presented by the transition to sustainable energy sources are explored, including the need for investment in renewable energy technologies, policy changes to incentivize sustainable energy use, and the potential for job creation in the sustainable energy sector. On the other hand, it is recognized that there are considerable hurdles that need to be addressed, including the substantial initial expenses associated with establishing renewable energy systems, as well as the political and societal barriers to enacting change. The economic benefits of transitioning to sustainable energy, such as improved energy security, reduced dependence on fossil fuels, and the potential for increased economic growth, are evaluated. The complex relationship between energy and the economy is thoroughly analyzed, presenting a valuable contribution to the academic literature on sustainable energy. Furthermore, an inquiry is being made into the potential contribution of blockchain technology in advancing a sustainable energy landscape. This includes its ability to augment the effectiveness and openness of energy markets, as well as its capacity to assist in the assimilation of renewable energy resources. Hence, this research underscores the importance of transitioning to sustainable energy sources for their environmental and economic merits. The findings presented offer valuable insights to inform policy decisions and guide future research endeavors in this field. By promoting the advancement of sustainable energy technologies, this study contributes to the development of a more sustainable global economy.